Virtual reality in the motion picture industry: The relationship among movie coolness, sympathy, empathy, and word-of-mouth - Rodrigues, M.; Loureiro, S. M. C. (Journal of Promotion Management, 2022)
The current study aims to explore whether virtual reality can be more effective that traditional 2 D in influencing empathy, sympathy, movie coolness and word-of-mouth. A factorial design 2 (movie story: documentary, animation) x 2 (technology format: 2 D, VR) between-subjects experiment approach was employed. The 2 D counterparts are available on YouTube and the VR version was downloaded to be experienced with the Oculus Rift headset device. A total of 145 participants were recruited. Findings reveal the combined effects of technological format and movie genre have a significant influence on coolness perception. Empathy influence movie coolness and these, in turn, predict word-of-mouth.